2015
DOI: 10.1080/13803395.2014.1002759
|View full text |Cite
|
Sign up to set email alerts
|

Exploring strategies to operationalize cognitive reserve: A systematic review of reviews

Abstract: This review highlights the lack of consensus regarding a definition of cognitive reserve. Further research is required to clarify how the indicators already identified may provide cognitive reserve and offer a protective effect against dementia. Agreement on the indicators that constitute the cognitive reserve model is needed before testing possible interventions that may increase the reserve supply and improve cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
100
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 38 publications
(99 reference statements)
7
100
0
9
Order By: Relevance
“…Education might also reflect a better socioeconomic status and thus a better access to healthcare. Nevertheless, these other markers of cognitive reserve might have the same limitations as the educational level, and education remains the most used measure of cognitive reserve in existing literature [36,37,38]. Second, we could not adjust for brain reserve in our study, since brain volumes were not available in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education might also reflect a better socioeconomic status and thus a better access to healthcare. Nevertheless, these other markers of cognitive reserve might have the same limitations as the educational level, and education remains the most used measure of cognitive reserve in existing literature [36,37,38]. Second, we could not adjust for brain reserve in our study, since brain volumes were not available in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps people with higher education and, consequently, higher cognitive reserve are more resilient to the damage caused by a stroke or TIA either due to better efficiency or more capacity or flexibility of brain networks already present before the damage (neural reserve) or because of better compensation for the damage (neural compensation). Neural compensation pertains to the ability of persons with higher cognitive reserve, to form collateral networks in the brain, when the usual neuronal networks are compromised by the vascular damage [4,36,37]. Studies have suggested that cognitively stimulating activities, which are mostly experienced during education, not only promote neurogenesis but also upregulate brain-derived neurotrophic factor, which in turn promotes plasticity [3,37].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans have also demonstrated a link between music training early in life and better auditory processing skills later in life, especially in challenging listening environments (39)(40)(41). Although early training in younger life has been shown to confer enduring neurobehavioral advantages and to contribute to positive brain health benefits sustained into older ages, scientists still incompletely understand the basis of this "cognitive reserve" (42,43). However, higher SOP, the accurate reception of target stimuli in the presence of confusable distractors, and the retained connectional integrity of forebrain systems, all of which were intensely engaged by our simple training task, provide key indices of the measured level of protection that is commonly attributed to this "reserve" (2,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…At best, attempts to operationalise and measure CR (Harrison et al, 2015) represent proxy measures with differing levels of construct validity. Various studies have used single proxy measures to infer the impact of CR on cognitive performance and rate of age-related cognitive decline.…”
Section: Introductionmentioning
confidence: 99%